2012
DOI: 10.1038/ajg.2012.254
|View full text |Cite
|
Sign up to set email alerts
|

Linaclotide for Irritable Bowel Syndrome With Constipation: A 26-Week, Randomized, Double-blind, Placebo-Controlled Trial to Evaluate Efficacy and Safety

Abstract: This guidance represents the Food and Drug Administration's (FDA's) current thinking on this topic. It does not create or confer any rights for or on any person and does not operate to bind FDA or the public. You can use an alternative approach if the approach satisfies the requirements of the applicable statutes and regulations. If you want to discuss an alternative approach, contact the FDA staff responsible for implementing this guidance. If you cannot identify the appropriate FDA staff, call the appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
405
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(455 citation statements)
references
References 30 publications
35
405
2
6
Order By: Relevance
“…These findings are consistent with the earlier studies. 3,4 The most impressive difference between our study and their study is discontinuation rate of linaclotide. We can understand that randomized controlled trial is more ideal clinical situation than daily practice.…”
mentioning
confidence: 65%
“…These findings are consistent with the earlier studies. 3,4 The most impressive difference between our study and their study is discontinuation rate of linaclotide. We can understand that randomized controlled trial is more ideal clinical situation than daily practice.…”
mentioning
confidence: 65%
“…Interestingly, the correlation between aggregate measures of published studies addressing bowel patterns and pain correspond with results of a pilot study, which demonstrated a significant relationship between changes in bowel frequency and pain ratings for individual patients receiving linaclotide for constipation. 62 The described correlation between improved pain ratings were not only reported in studies of the newly introduced agents for IBS-C, [63][64][65][66][67] but were also observed in many other trials, which did not meet inclusion criteria for this analysis and examined the effects of interventions ranging from fiber supplements, 68,69 to herbal preparations, 70 biofeedback, 71 bisacodyl, 72 or osmotic laxatives. [73][74][75] While not the focus of this analysis, we noted some statistically significant, but clinically minor, differences in the endpoints between patient cohorts with constipation and IBS-C.…”
Section: Discussionmentioning
confidence: 99%
“…An intracellular cascade of events leads to activation of chloride secretion and thereby a net movement of water into the gut lumen, resulting in softer stool and more frequent bowel movements [27]. A feature of particular interest relates to reductions in constipation associated abdominal pain [28] and bloating [29], which can develop gradually over months from the start of treatment.…”
Section: Constipationmentioning
confidence: 99%